Importancia de la utilización del antisuero cde como control de calidad en la identificación de los fenotipos del sistema rh en mujeres de edad fértil atendidas en el banco de sangre de riobamba, durante el período de enero a junio del 2010 - Ortega Samaniego, Silvana Maribel (2010)
The study of blood includes assessing alterations of its components in form, quantity, functions. But the study of this vital component to compensate any of its components through specialized studies within the field of Immunohematology. A blood group system consists of antigens produced both directly and indirectly. Later they found another group of antigens called Rhesus factor (Rh factors) because they were discovered during experiments on Rhesus monkeys.